Full spectrum filterless fluorescence microscopy. - Booth, M; Jesacher, A; Juskaitis, R; Wilson, T (2010)
In conventional microscopes, fluorescence emission is separated from the backscattered illumination using the Stokes shift, whereby the emission occurs at a longer wavelength to the excitation. Such separation is usually achieved through a combination of wavelength filters that divide the spectrum into mutually exclusive excitation and emission bands. It is therefore impossible in these microscopes to access the full excitation/emission spectrum of the specimen in a single image. We report on a microscope that acquired fluorescence images using illumination across the spectral range 450-680 nm; the full emission spectrum was detected simultaneously across the same range. The microscope was also combined with structured illumination optical sectioning to give three-dimensionally resolved images with improved background rejection. Full spectrum fluorescence images of biological specimens are demonstrated. As this system is more versatile than the standard fluorescence microscope, it could be of benefit in many fluorescence imaging applications.